Endotoxin-minimized HIV-1 p24 fused to murine hsp70 activates dendritic cells, facilitates endocytosis and p24-specific Th1 response in mice - Krupka, M; Zachova, K; Cahlikova, R; Vrbkova, J; Novak, Z; Sebela, M; Weigl, E; Raska, M (Immunology letters, 2015)
Heat shock proteins hsp70 and gp96 have been confirmed as adjuvants enabling induction of cell- and antibody-mediated immunity specific to associated protein or peptide antigens due to the activation of naive dendritic cells and supporting cross-presentation of associated antigen. An efficacious vaccine preventing HIV-1 infection should induce (1) antibodies neutralizing HIV-1 Env protein, preventing virus spreading and (2) CD4(+) Th1 and CD8(+) T cells specific to viral proteins, especially gag p24, important for elimination of HIV-1 infected cells. As p24 is relatively poorly recognized by dendritic cells, its targeting to DC is important for enhancement of vaccine efficacy. In this study, a p24 protein fused to the C- or N-terminus of murine hsp70 was produced as a recombinant protein and administered without any adjuvant to experimental BALB/c mice. Consequently, p24-specific cellular and humoral immune responses were measured. To minimize the effect of bacterial endotoxin, each protein was subjected to a repeated endotoxin phase extraction until each preparation contained less than 2.5 endotoxin unit (EU) per mg of antigen. In addition, endocytosis of p24 fused to hsp70 by dendritic cells and their activation were characterized. The fusion to hsp70 protein enhanced endocytosis of p24 as well as activation of dendritic cells in vitro. After immunization of mice, hsp70-p24 fusion protein induced the strongest p24-specific CD4(+) and CD8(+) T cells (IFN-γ production) and humoral (IgG2b) responses corresponding to Th1 type dominance, whereas p24-hsp70 or p24 itself induced weaker responses.
Keywords: Mice, Inbred BALB C; Endocytosis; endotoxiny; vakcíny proti AIDS; HSP70 Heat-Shock Proteins; Mice; Endotoxins; endocytóza; Th1 Cells; HIV-1 protein p24; Dendritic Cells; HIV Core Protein p24; CD8-pozitivní T-lymfocyty; Antigens, Viral; dendritické buňky; ženské pohlaví; Immunization; zvířata; Cross-Priming; Th1 buňky; Vaccine; Recombinant Fusion Proteins; myši inbrední BALB C; nepřímá aktivace; rekombinantní fúzní proteiny; HIV; Heat shock protein; HIV korový protein p24; myši; antigeny virové; AIDS Vaccines; imunizace; CD8-Positive T-Lymphocytes; proteiny tepelného šoku HSP70; Female; Animals